Pencegahan Kekerasan Dalam Olaraga: Pendekatan Edukasi Dan Hukum Keolaragaan Bagi Komunitas Olahraga Lokal Di Kelurahan Bontoraya - Munandar, Wahyu (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Violence in football has increased in the last decade. This phenomenon is not only studied sociologically, but also through a legal approach. The socialization of activities was carried out in Bontoraya Village, Batang District, Jeneponto Regency. The approach used in this Community Service activity is an educational approach and a sports law approach, where this approach is used to examine the riots that usually occur in sports events and transform them into regulations or laws on violence in football. Violence can be committed by anyone, and the consequences must be understood. Therefore, it is necessary to conduct socialization to the Local Sports Community in Bontoraya Village that this violence is a criminal act or ordinary violation. The material for this socialization aims to improve sports values ​​to reduce violence at sporting events.